Addition of 1-Hydroxyalkyl Free Radicals to Unsolvated Formaldehyde in Alcohol–Formaldehyde Solutions with Nonbranched-Chain Formation of 1,2-Alkanediols - Silaev, Michael M. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
A mechanism of the initiated nonbranched-chain process of forming 1,2-alkanediols and carbonyl compounds in alcohol–formaldehyde systems is suggested. The quasi-steady-state treatment is used to obtain kinetic equations that can describe the nonmonotonic (with a maximum) dependences of the formation rates of the products on the concentration of free unsolvated formaldehyde. The experimental concentration of the free unsolvated form of formaldehyde are given at the different temperatures, solvent permittivity, and total concentrations of formaldehyde in water and alcohols. An empirical equation for calculating the free formaldehyde concentration in alcohol–formaldehyde (including water/ethanediol–formaldehyde) systems at various temperatures and total formaldehyde concentrations and an equation for evaluating solvent concentrations in these systems were derived.